Birth Restriction In The Perspective Of The Qur'an - naseh ulwan; Kholilurrohman; Zakaria Husin Lubis (Sufiya Research Institute, 2023)
Birth restrictions in the Al-Qur'an perspective are permanent birth restrictions prohibited in the Al-Qur'an because they are contrary to human nature, namely having offspring. However, in emergency situations, the Qur'an provides relief or allows birth restrictions to maintain maternal health. The discourse around birth control is currently increasingly urgent if it is related to the dense population of the world, especially the Indonesian population. Indonesia's population has now reached 270 million people with a population density of 140 people per square kilometer. If population density is not balanced with the State's ability to control it, it will give rise to problems such as poverty, health, education and crime. Therefore, in an emergency, birth control is one of the preventive options to reduce the rate of population growth. The problem that often arises when discussing the issue of limiting offspring is the quantity and quality of the population. This was triggered by the understanding that children are a gift from Allah and on the Day of Judgment the Messenger of Allah will be proud to see his many people. This understanding provides motivation for people to increase their offspring. However, on the one hand, Allah reminds us not to leave behind a weak generation, fearing that it will burden the family and the country.